Assessing the Mode of Biblical Interpretation in the Light of African Biblical Hermeneutics: The Case of the Mother-Tongue Biblical Interpretation in Ghana - Antwi, Emmanuel Kojo Ennin ca. 20./21.Jh. (Religions, 2024)
In establishing the Christian faith on African soil, the first missionaries to Africa came along with the Bible. They were determined to share the word of God with the indigenous Africans. This was undertaken effectively; however, it came at a cost. In an attempt to produce translated versions of the Bible for the natives, they ended up producing translations, some of which did not reflect the thoughts of the indigenous people. This has called for an enterprise whereby these texts need to be retranslated and interpreted to reflect the thoughts of the indigenous people. Mother-tongue biblical hermeneutics in Ghana has been advantageous to this enterprise since it seeks to remedy the situation by examining the mother-tongue translations and making proposals for retranslations and interpretation. This has attracted some scholars to come up with a methodology and approaches that would be appropriate in this direction. This paper seeks to assess and evaluate the use of the mother-tongue interpretation, as well as its methodology and approaches in Ghana in the light of African biblical hermeneutics. Though this enterprise is recommendable to African exegetes, it is a special area of biblical studies in search of a standard methodological approach. The paper calls for much attention to how the mother-tongue interpretation could bring the meaning of the text closer to the culture of the Ghanaian reader—however, not at the expense of neglecting the cultural milieu of the original author in which the text was couched.